Nutritional Assessment of Different Field Pea Genotypes (Pisum sativum L.) - Rodrigues, A.M. (2012)
The aim of this study was to determine the dry matter (DM), ash, organic matter (OM), crude protein (CP), ether extract (EE), crude fiber (CF), total sugars, starches and estimate the metabolizable energy (ME), in ruminants, pigs, poultry, horses and pets (dogs and cats) and digestible energy (DE) in rabbits from the 10 most productive field pea genotypes (Pisum sativum) obtained in a trial with 4 X 20 different genotypes (Project 0186_AGROCELE_3_E). The results (% DM - genotype) allowed us to state the following: all the 10 field pea genotypes grain were an important source of energy (cytoplasmic carbohydrates) with high percentages of soluble sugars (7.95% ISARD to 9.42% ENDURO) (P < 0.05) and starch (38.63% LIVIA to 45.00% AUDIT) (P < 0.05), low CF content (5.99% ISARD to 7.90% CARTOUCHE) (P < 0 05), high CP (22.8% ENDURO to 26.1% CORRENT) (P < 0.05), low levels of EE (0.69% LIVIA to 1.62% CHEROKEE) (P<0.05), ideal level of ME ruminants (11.844 MJ/kg DM - CHEROKEE to 11.883 MJ/kg DM - CORRENT) (P < 0.05), ME pigs (14.683 MJ/kg DM - ISARD to 13.885 MJ/kg DM - CARTOUCHE) (P < 0.05), ME poultry (11.540 MJ/kg DM - LIVIA to 12.868 MJ/kg DM - AUDIT) (P < 0.05), ME horse (11.392 MJ/kg DM - CORRENT to 11.979 MJ/kg DM - AUDIT) (P < 0.05), ME pets (13.116 MJ/kg DM – CORRENT to 13.498 MJ/kg DM - ISARD) (P < 0.05) and DE rabbits (12.977 MJ/kg DM – CARTOUCHE to 13.044 MJ/kg DM - ISARD) (P < 0.05). We concluded that all 10-field pea genotypes are an excellent feedstuff for ruminants and non-ruminants animal and it could be supplied plain or included in concentrate feed because it is an excellent protein and energy supplement. It combines in the same grain high levels of crude protein and starch. Due to the low fat content is a very interesting pulse for pets’ light diets.